2011
DOI: 10.1088/0031-9155/56/9/011
|View full text |Cite
|
Sign up to set email alerts
|

MicroCT with energy-resolved photon-counting detectors

Abstract: The goal of this paper was to investigate the benefits that could be realistically achieved on a microCT imaging system with an energy-resolved photon-counting x-ray detector. To this end, we built and evaluated a prototype microCT system based on such a detector. The detector is based on cadmium telluride (CdTe) radiation sensors and application-specific integrated circuit (ASIC) readouts. Each detector pixel can simultaneously count x-ray photons above six energy thresholds, providing the capability for ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 21 publications
(28 reference statements)
0
87
0
Order By: Relevance
“…State of the art photon-counting detectors based on semiconductors such as silicon, [30][31][32][33][34] cadmium telluride (CdTe) 27,[35][36][37][38] and cadmium-zinc-telluride (CZT) 29,39-41 offer a maximum count rate over 10 7 (counts/s)/mm 2 . [42][43][44] However, the detector response may become nonlinear under such high count rates due to various artifacts such as pulse pileup, characteristic escape, and charge-sharing.…”
Section: Introductionmentioning
confidence: 99%
“…State of the art photon-counting detectors based on semiconductors such as silicon, [30][31][32][33][34] cadmium telluride (CdTe) 27,[35][36][37][38] and cadmium-zinc-telluride (CZT) 29,39-41 offer a maximum count rate over 10 7 (counts/s)/mm 2 . [42][43][44] However, the detector response may become nonlinear under such high count rates due to various artifacts such as pulse pileup, characteristic escape, and charge-sharing.…”
Section: Introductionmentioning
confidence: 99%
“…For energies below 30 keV, the measured counts were significantly higher than the simulated spectrum, most likely due to charge sharing effect. 20 However, in the intermediate energy range, the measured counts were comparably smaller. Finally, the measured counts in higher energy region exceeded that of the simulated spectrum and extended over the maximum tube voltage of 100 kVp.…”
Section: Iic3 Quantitative Materials Decompositionmentioning
confidence: 95%
“…34,35 Another approach, which has been widely used in studies on photon-counting detectors, sets the highest energy thresholds at the maximum tube voltage; thus, any pulse exceeding the threshold will be counted in the last energy bin (pileup bin) and excluded from data acquisition. 6,20 However, pulse pileup cannot be effectively eliminated in this approach because it can also occur below the maximum tube voltage. Furthermore, the dose efficiency will be reduced since photons registered in the pileup bin will not contribute to the imaging task.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multienergy discrimination is extremely sensitive on the chemical composition of the material. A seminal work has been done in 2003 by Pacella et al 43,44 in developing X-ray imaging detectors based on gas electron multipliers, with energy resolution capability. Pacella et al 45 demonstrated in 2006 that energy-resolved imaging is a powerful way to distinguish materials that cannot be discriminated with the standard (energy integrated) X-ray imaging, and even more, it could reveal the nature of the material despite the poor energy resolution of the detector.…”
Section: Energy-resolved Imagingmentioning
confidence: 99%